New knowledge on how dairy cattle milk yield is affected by heat stress, in smallholder systems in East Africa. - CGIAR Research Program on Livestock (2020)
Evaluating the impact of heat stress as measured by temperature-humidity index (THI) on test-day milk yield of small holder dairy cattle in a sub-Saharan African climate.